A Complex Structure in the northwestern of Sumatra Fore-arc. Issue 1 (June 2021) - Priyanto, W S; Permana, H; Arisa, D; Aulia, A; Mukti, M M; Handayani, L; Farisan, A
Abstract: The Sumatran offshore region is known as an active seismogenic zone. Consequently, there were many records of great events that caused a big catastrophe, such as the 2004 Sumatra-Andaman earthquake. In order to investigate the geometry and nature of the earthquake ruptures and structures, we utilize the bathymetry and Multi-Channel Seismic (MCS) profiles from the SO-198 research project in 2008 (R/V Sonne) and KH-10-5 research project in 2010 (R/V Hakuho-Maru). We find that the area along the Sunda Trench to the fore-arc high in the northwestern Sumatra are characterized by parallel anticlinal ridges with distinctive vergence regimes. These vergence regimes classified as seaward, mix and landward vergence system. Our data interpretation recognized structures such as Main thrust, Lower thrust, Middle thrust, Upper thrust, piggy-back basin and West Andaman Fault within this region. Our conclusion suggest that the anticlinal seaward and landward vergence are considered as the product of recent deformation rupture. The co-seismic slip from the past earthquake ruptures tends that it was occurred from the deeper part in the entire northwestern of Sumatra fore-arc.